PENDAMPINGAN KESADARAN BERBANGSA DAN BERNEGARA DALAM MENINGKATKAN JIWA NASIONALISME MASYARAKAT KAMPUNG YANGGANDUR - Hesty Tambajong; Jeni Paresa; Fransin Kontu; Rachmat Agung Puank Parukka; Hubertus Oja (Musamus Devotion Journal, 2023)
Yanggandur Village is a village directly adjacent to the country of Papua New Guinea, where most of the Kanum people in the village practice mixed marriages with the Kanum people who are in the country of Papua New Guinea. Judging from the culture and perspective of society which is still very limited, one step taken by the government is to strengthen education and understanding in shaping the community to become Indonesian citizens who have a national outlook and have a spirit of nationalism and love for Indonesia's homeland so that it is not easily infiltrated by other views. which can break the defense of the unity and integrity of the Indonesian state. This study aims to find out strategies about understanding the life of a good nation and state. Data collection techniques are observation, interviews, and documentation. The results of the study show that the assistance for understanding the life of the nation and state in Yanggandur Village has not run optimally. In understanding the change in mindset, society is still conservative and very passive with the situations that occur in the surrounding environment. Then fostering the spirit of nationalism, coaching needs to be improved in a sustainable manner in order to increase the spirit of nationalism, so as to form the mindset of the Indonesian people who have the spirit of Pancasila